2009
DOI: 10.1111/j.1651-2227.2008.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prevalence of low birth weight in Okinawa, Japan: a public health perspective

Abstract: Japan is unique among developed countries in that the LBW rate has almost doubled in the past three decades and the rate in Okinawa is 20% greater than the mainland. The health costs of this trend include the neonatal care of LBW infants and the increased risk of chronic disease in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…The U.S. National Center for Health Statistics points out that mortality for gestational agespecific (22-36 weeks) preterm infants in the United States compares favorably with those in Europe, but for infants born at 37 weeks or more, the United States has higher mortality (74). Japan has similar PTB rates to those in Europe, much higher rates of low birth weight (considerably higher than in the United States), but better infant mortality outcomes (7,46,74,89,98,102,126).…”
Section: International Rankings Of Population Health Measuresmentioning
confidence: 98%
“…The U.S. National Center for Health Statistics points out that mortality for gestational agespecific (22-36 weeks) preterm infants in the United States compares favorably with those in Europe, but for infants born at 37 weeks or more, the United States has higher mortality (74). Japan has similar PTB rates to those in Europe, much higher rates of low birth weight (considerably higher than in the United States), but better infant mortality outcomes (7,46,74,89,98,102,126).…”
Section: International Rankings Of Population Health Measuresmentioning
confidence: 98%
“…2.5 kg) in Okinawa than in Japan for decades (e.g. in 1973, 8.1% in Okinawa and 6% in Japan [12] ). It has been argued that the lower infant mortality rate in Okinawa than in Japan before WW2 indicated that, probably, the low birthweight rate was also lower but, due to the war destructions [6] , no data are available for the period before WW2 and, unfortunately, no data on birthweight were gathered under the American military administration, before the reversion of Okinawa to Japan in 1972.…”
Section: Dietary Restriction Studies In Humansmentioning
confidence: 99%
“…However, Japan is an 'exception' in that it presents one of the highest low birth weight with one of the lowest infant mortality rate. Whereas the prevalence of low birth weight has increased in several OECD countries (OECD, 2009a), Japan is unique among developed countries in that the low birth weight rate has almost doubled in the past three decades (Hokama and Binns, 2009) passing from 5 per cent in the late 1970s to almost 10 per cent in the late 2000s. Possible causes include an increase in smoking among younger women (Ohmi et al, 2001) and the tendency to have children at older ages (Jeong and Hurst, 2001).…”
Section: Healthmentioning
confidence: 99%